Composite graphite-based material for bipolar plate and preparation method of composite graphite-based material

By mixing graphite, 4- (1-基 oxygen-5-decido-oxygenyl) butyl tritenomonium bromide, conductive and resin mixing in a specific proportions, and using ball mill and heat pressure molding method to prepare a composite graphite base Materials solve the problems that the bipolar board conductivity, gas tightness and mechanical strength are difficult to take into account, and realize higher conductivity, gas tightness and mechanical strength.

CN119361736AInactive Publication Date: 2025-01-24DONGGUAN JIAYU CARBON PROD CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411477557.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult for existing composite graphite-based materials to take into account the conductivity, airtightness and mechanical strength of bipolar plates.

Method used

Graphite, 4- (1-cymbal oxygen-5-decido-oxygenyl) butyl tritenoblobar acetomizer, conductive and resin mix in a specific proportion, and prepare composite graphite-based materials through ball mills and thermal pressure molding methods.

Benefits of technology

The electrical conductivity, air tightness and mechanical strength of the bipolar plate are improved, a more continuous and tighter conductive network is formed, and the toughness and air tightness of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096515650000041
    Figure BDA0005096515650000041
  • Figure BDA0005096515650000042
    Figure BDA0005096515650000042
  • Figure BDA0005096515650000071
    Figure BDA0005096515650000071
Patent Text Reader

Abstract

The invention provides a composite graphite-based material for a bipolar plate and a preparation method thereof, and the composite graphite-based material for the bipolar plate is prepared from the following raw materials in parts by weight: 80 to 100 parts of graphite, 8 to 15 parts of 4-(1-naphthyloxy-5-decyloxy) butyl trimethyl ammonium bromide, 5 to 10 parts of conductive agent and 10 to 30 parts of resin. The composite graphite-based material for the bipolar plate has good conductivity, air tightness and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bipolar plate materials for fuel cells, and in particular to a composite graphite-based material for bipolar plates and a preparation method thereof. Background Art

[0002] Fuel cells are a key industry in the field of new energy and can be widely used in the fields of automobiles, aerospace, military, various electronic smart terminals, etc. In fuel cells, bipolar plates are one of the core components, and their main functions are to separate the reaction gases, evenly introduce the reaction gases, collect and conduct current, support the membrane electrode, and achieve rapid drainage and heat dissipation of the fuel cell system.

[0003] At present, the most widely used bipolar plate material is graphite bipolar plate, which specifically includes carved hard graphite bipolar plate, flexible graphite bipolar plate, and composite graphite bipolar plate. Among them, composite graphite bipolar plate has the advantages of one-time molding and simple process, so it has good prospects for industrial large-scale production.

[0004] Composite graphite-based materials are made by hot pressing graphite powder and adhesive resin. Graphite powder has good electrical conductivity, but pure graphite plate has poor mechanical strength and is difficult to meet the air tightness requirements of bipolar plates. It is necessary to add adhesive resin to improve mechanical strength and air tightness. The high conductivity of bipolar plates requires an increase in graphite content, but the air tightness and mechanical strength of bipolar plates require an increase in resin content.

[0005] In view of this, there is an urgent need to propose a composite graphite-based material for bipolar plates that can better balance the conductivity, air tightness and mechanical strength of the bipolar plates. Summary of the invention

[0006] The object of the present invention is to provide a composite graphite-based material for a bipolar plate, so as to solve the problem that the composite graphite-based material in the prior art is difficult to take into account the conductivity, air tightness and mechanical strength of the bipolar plate.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0008] A composite graphite-based material for a bipolar plate comprises the following raw materials in parts by weight:

[0009] 80-100 parts of graphite, 8-15 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 5-10 parts of conductive agent, and 10-30 parts of resin.

[0010] Preferably, the resin is a phenolic resin or a mixture of a phenolic resin and an epoxy resin.

[0011] Preferably, the conductive agent is polyaniline.

[0012] The invention provides a method for preparing a composite graphite-based material for a bipolar plate, comprising the following steps: uniformly mixing graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, a conductive agent and a resin, and hot pressing and molding.

[0013] Preferably, the method for preparing the composite graphite-based material for bipolar plates comprises the following steps:

[0014] (1) taking graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water, mixing them uniformly to obtain a mixed solution;

[0015] (2) taking a resin, a conductive agent, and a dispersant, mixing them evenly, adding them to the mixed solution obtained in step (1), mixing evenly, and obtaining a mixed slurry;

[0016] (3) drying and hot pressing the mixed slurry obtained in step (2) to obtain a product.

[0017] Preferably, in step (1), the mass percentage of water in the mixed liquid is 10-15wt%.

[0018] Preferably, step (1) is as follows: graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water are mixed evenly, and the obtained mixed solution is ball-milled at a rotation speed of 500-800 r / min for 30-90 min.

[0019] Preferably, in step (2), the dispersant is acetone; and the mass ratio of the acetone to the resin is (1.5-2.0):1.

[0020] Preferably, in step (3), the drying temperature is 60-70° C. and the drying time is 2-4 h.

[0021] Preferably, in step (3), the hot pressing molding is carried out at a pressure of 30-50 MPa and a temperature of 160-180° C. for 30-60 min.

[0022] The above solution of the present invention includes at least the following beneficial effects:

[0023] (1) The composite graphite-based material for bipolar plates of the present invention comprises the following raw materials in parts by weight: 80-100 parts of graphite, 8-15 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 5-10 parts of a conductive agent, and 10-30 parts of a resin. The composite graphite-based material for bipolar plates has good electrical conductivity, air tightness, and mechanical strength.

[0024] Wherein, the 4-(1-naphthyloxy-5-decyloxy) butyl trimethyl ammonium bromide has trimethyl ammonium ions, which can penetrate into the interlayer of the graphite through the cation-π effect, reduce the surface energy of the system, greatly improve the dispersibility of graphite in water, and reduce the agglomeration of graphite. At the same time, the naphthalene ring of naphthyloxy, as a condensed ring aromatic hydrocarbon, has a conjugated structure with the layered structure of graphite, has a good interfacial bonding force with the interlayer of graphite, and can maintain a relatively stable dispersed state. At the same time, the 4-(1-naphthyloxy-5-decyloxy) butyl trimethyl ammonium bromide, as a surfactant, has good compatibility with the resin, improves the contact area between the graphite and the resin in the mixed slurry, so that after hot pressing, a conductive path can be more fully formed to improve conductivity.

[0025] In particular, when the resin is a phenolic resin or contains a phenolic resin, the long-chain decyloxy and naphthyloxy groups of the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide can be close to the phenolic resin under the hydrophobic effect, so that the interfacial gap between the graphite and the resin is reduced, thereby reducing the interfacial resistance. In addition, the molecular structure of the phenolic resin is a mesh, and after molding, a three-dimensional mesh structure with a high degree of cross-linking is formed between the molecules, which has high mechanical strength and rigidity, strong stability, good heat resistance and chemical corrosion resistance, and no by-products are generated during the curing process. However, since it contains a large number of rigid benzene ring structures, the obtained bipolar plate has greater brittleness, and the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide has a flexible long-chain alkyl group, which can form a cross-linked structure with the resin, effectively transfer stress, improve the toughness of the composite material, and greatly improve the mechanical properties of the bipolar plate.

[0026] In addition, the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide enhances the interfacial bonding force between the graphite and the resin and adjusts the three-dimensional cross-linked structure formed by the resin, so that the structure of the sheet after thermosetting molding is more uniform and dense, which can effectively reduce the penetration channels of gas molecules, thereby improving air tightness.

[0027] (2) The composite graphite-based material for bipolar plates of the present invention, wherein the conductive agent is polyaniline. The 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide located between the graphite layers can be combined with the polyaniline particles through electrostatic action or hydrogen bonding due to the presence of quaternary ammonium salt molecules, so that the polyaniline is evenly distributed on the graphite surface, filling the gaps between the graphite particles, increasing the conductive contact points, and forming a more continuous and compact conductive network. At the same time, the steric hindrance effect generated by the long chain structure of the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is conducive to maintaining a certain distance between the polyaniline particles, so that they are evenly dispersed.

[0028] (3) The preparation method of the composite graphite-based material for bipolar plates of the present invention, step (1) is as follows: graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water are mixed evenly, and the obtained mixed solution is ball-milled at a speed of 500-800 r / min for 30-90 min. The physical shear force generated by ball milling causes the graphite layer to slide, thereby causing the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide to be more tightly and fully combined with the layered structure of the graphite, so that the 4-

[0029] (1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is uniformly intercalated between the graphite layers. DETAILED DESCRIPTION

[0030] In the embodiments of the present invention, if the specific conditions are not specified, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Raw materials of different manufacturers and models do not affect the implementation of the technical solution of the present invention and the realization of the technical effects.

[0031] The 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide described in the following examples has a structure as shown in formula (I):

[0032]

[0033] The 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is a product of the prior art and can also be prepared using the prior art. For example, it can be synthesized in the following manner:

[0034]

[0035] Example 1

[0036] The composite graphite-based material for the bipolar plate in this embodiment includes the following raw materials in parts by weight:

[0037] 80 parts of graphite, 8 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 10 parts of conductive agent, and 20 parts of resin.

[0038] Wherein, the resin is phenolic resin and the conductive agent is polyaniline.

[0039] The method for preparing the composite graphite-based material for bipolar plates described in this embodiment comprises the following steps:

[0040] (1) Graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water were mixed uniformly, and the resulting mixture was ball-milled at a speed of 600 r / min for 30 min;

[0041] The mass percentage of water in the mixed liquid is 15wt%.

[0042] (2) taking a resin, a conductive agent, and a dispersant, mixing them evenly, adding them to the mixed solution obtained in step (1), mixing evenly, and obtaining a mixed slurry;

[0043] Wherein, the dispersant is acetone; the mass ratio of the acetone to the resin is 1.5:1.

[0044] (3) drying and hot pressing the mixed slurry obtained in step (2) to obtain a product.

[0045] The drying temperature is 65° C. and the drying time is 2 hours. The hot pressing molding is performed at a pressure of 40 MPa and a temperature of 160° C. for 45 minutes.

[0046] Example 2

[0047] The composite graphite-based material for the bipolar plate in this embodiment includes the following raw materials in parts by weight:

[0048] 100 parts of graphite, 10 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 5 parts of conductive agent, and 30 parts of resin.

[0049] The resin is a mixture of phenolic resin and epoxy resin in a weight ratio of 1:1. The conductive agent is polyaniline.

[0050] The method for preparing the composite graphite-based material for bipolar plates described in this embodiment comprises the following steps:

[0051] (1) graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water were mixed uniformly, and the obtained mixture was ball-milled at a speed of 800 r / min for 90 min;

[0052] The mass percentage of water in the mixed liquid is 12wt%.

[0053] (2) taking a resin, a conductive agent, and a dispersant, mixing them evenly, adding them to the mixed solution obtained in step (1), mixing evenly, and obtaining a mixed slurry;

[0054] Wherein, the dispersant is acetone; the mass ratio of the acetone to the resin is 2.0:1.

[0055] (3) drying and hot pressing the mixed slurry obtained in step (2) to obtain a product.

[0056] The drying temperature is 70° C. and the drying time is 4 hours. The hot pressing molding is performed at a pressure of 30 MPa and a temperature of 180° C. for 60 minutes.

[0057] Example 3

[0058] The composite graphite-based material for the bipolar plate in this embodiment includes the following raw materials in parts by weight:

[0059] 90 parts of graphite, 15 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 8 parts of conductive agent, and 10 parts of resin.

[0060] Wherein, the resin is phenolic resin and the conductive agent is polyaniline.

[0061] The method for preparing the composite graphite-based material for bipolar plates described in this embodiment comprises the following steps:

[0062] (1) Graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water are mixed uniformly, and the resulting mixture is ball-milled at a speed of 500 r / min for 60 min;

[0063] The mass percentage of water in the mixed liquid is 10wt%.

[0064] (2) taking a resin, a conductive agent, and a dispersant, mixing them evenly, adding them to the mixed solution obtained in step (1), mixing evenly, and obtaining a mixed slurry;

[0065] Wherein, the dispersant is acetone; the mass ratio of the acetone to the resin is 1.8:1.

[0066] (3) drying and hot pressing the mixed slurry obtained in step (2) to obtain a product.

[0067] The drying temperature is 60°C and the drying time is 3 hours. The hot pressing molding is carried out at a pressure of 50 MPa and a temperature of 170°C for 30 minutes.

[0068] Example 4

[0069] The composite graphite-based material for the bipolar plate in this embodiment includes the following raw materials in parts by weight:

[0070] 100 parts of graphite, 12 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 10 parts of conductive agent, and 20 parts of resin.

[0071] Wherein, the resin is phenolic resin and the conductive agent is polyaniline.

[0072] The method for preparing the composite graphite-based material for bipolar plates described in this embodiment comprises the following steps:

[0073] (1) graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water were mixed uniformly, and the obtained mixture was ball-milled at a speed of 800 r / min for 90 min;

[0074] The mass percentage of water in the mixed liquid is 15wt%.

[0075] (2) taking a resin, a conductive agent, and a dispersant, mixing them evenly, adding them to the mixed solution obtained in step (1), mixing evenly, and obtaining a mixed slurry;

[0076] Wherein, the dispersant is acetone; the mass ratio of the acetone to the resin is 1.6:1.

[0077] (3) drying and hot pressing the mixed slurry obtained in step (2) to obtain a product.

[0078] The drying temperature is 70° C. and the drying time is 4 hours. The hot pressing molding is performed at a pressure of 50 MPa and a temperature of 175° C. for 60 minutes.

[0079] Comparative Example 1

[0080] The composite graphite-based material for bipolar plates in this comparative example is the same as that in Example 4 and is prepared by the same method, except that the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is not included.

[0081] Comparative Example 2

[0082] This comparative example is the same as the composite graphite-based material for bipolar plates in Example 4 and is prepared by the same method, with the only difference being that the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is replaced by 4-(1-naphthyloxy-5-octyloxy)butyltrimethylammonium bromide.

[0083] The 4-(1-naphthyloxy-5-octyloxy)butyltrimethylammonium bromide has the following structural formula:

[0084]

[0085] Comparative Example 3

[0086] The composite graphite-based material for bipolar plates in this comparative example is the same as that in Example 4 and is prepared by the same method, with the only difference being that the conductive agent is not included.

[0087] Comparative Example 4

[0088] The composite graphite-based material for bipolar plates in this comparative example is the same as that in Example 4 and is prepared by the same method, with the only difference being that the polyaniline in the conductive agent is replaced by conductive carbon black.

[0089] Comparative Example 5

[0090] The composite graphite-based material for bipolar plates in this comparative example is the same as that in Example 4 and is prepared by the same method, with the only difference being that the amount of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide used is 6 parts.

[0091] Comparative Example 6

[0092] The composite graphite-based material for bipolar plates in this comparative example is the same as that in Example 4 and is prepared by the same method, with the only difference being that the amount of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide used is 20 parts.

[0093] Effect experiment example

[0094] In order to verify the technical effect of the composite graphite-based material for bipolar plates described in the present invention, the following experiments were conducted:

[0095] The composite graphite-based materials for bipolar plates prepared in Examples 1-4 and Comparative Examples 1-6 were molded into plates with a thickness of 1.2 mm. The conductivity was measured using a conductivity meter, the bending strength was measured using an electronic universal testing machine, and the hydrogen permeability was measured using a permeation cell and a gas chromatograph.

[0096] After experimentation, the results are as follows:

[0097]

[0098] According to the results of Examples 1-4 and Comparative Examples 1-6, the composite graphite-based material for bipolar plates of the present invention has good electrical conductivity, mechanical properties and air tightness.

[0099] According to the results of Example 4 and Comparative Examples 1, 5 and 6, the addition of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide has a significant effect on the electrical conductivity, flexural strength and hydrogen permeability of the material. If the amount of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is too small, the effect of improving the electrical conductivity, flexural strength and air tightness of the material is not significant enough. If the amount of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide is too large, the electrical conductivity, flexural strength and air tightness of the material will be reduced to a certain extent, especially the electrical conductivity will decrease significantly.

[0100] According to the results of Example 4 and Comparative Example 2, replacing the 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide with 4-(1-naphthyloxy-5-octyloxy)butyltrimethylammonium bromide, that is, reducing the length of the long chain, will lead to a decrease in the overall performance of the bipolar plate. This may be due to certain differences in the steric hindrance generated and the interface interaction sites provided by alkyl chains of different lengths.

[0101] According to the results of Example 4 and Comparative Examples 3 and 4, the use of the polyaniline as a conductive agent not only has a significant impact on the conductivity of the material, but also has a certain impact on the mechanical properties and air tightness of the material.

[0102] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are encompassed by the present invention.

Claims

1. A composite graphite-based material for a bipolar plate, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of graphite, 8-15 parts of 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, 5-10 parts of conductive agent, and 10-30 parts of resin.

2. The composite graphite-based material for bipolar plates according to claim 1, characterized in that: The resin is a phenolic resin or a mixture of a phenolic resin and an epoxy resin.

3. The composite graphite-based material for bipolar plates according to claim 1, characterized in that: The conductive agent is polyaniline.

4. A method for preparing a composite graphite-based material for a bipolar plate according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide, a conductive agent and a resin uniformly, and hot pressing and forming the mixture.

5. The method for preparing a composite graphite-based material for a bipolar plate according to claim 4, characterized in that: The steps include: (1) taking graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water, mixing them uniformly to obtain a mixed solution; (2) taking a resin, a conductive agent, and a dispersant, mixing them evenly, adding them to the mixed solution obtained in step (1), mixing evenly, and obtaining a mixed slurry; (3) drying and hot pressing the mixed slurry obtained in step (2) to obtain a product.

6. The method for preparing a composite graphite-based material for a bipolar plate according to claim 5, characterized in that: In step (1), the mass percentage of water in the mixed solution is 10-15wt%.

7. The method for preparing a composite graphite-based material for a bipolar plate according to claim 5, characterized in that: Step (1) is specifically as follows: graphite, 4-(1-naphthyloxy-5-decyloxy)butyltrimethylammonium bromide and water are mixed evenly, and the obtained mixed solution is ball-milled at a rotation speed of 500-800 r / min for 30-90 min.

8. The method for preparing a composite graphite-based material for a bipolar plate according to claim 5, characterized in that: In step (2), the dispersant is acetone; the mass ratio of the acetone to the resin is (1.5-2.0):

1.

9. The method for preparing a composite graphite-based material for a bipolar plate according to claim 5, characterized in that: In step (3), the drying temperature is 60-70° C. and the drying time is 2-4 hours.

10. The method for preparing a composite graphite-based material for a bipolar plate according to claim 5, characterized in that: In step (3), the hot pressing molding is carried out at a pressure of 30-50 MPa and a temperature of 160-180° C. for 30-60 minutes.

Citation Information

Patent Citations

  • Compositions for bipolar plates and methods for manufacturing said compositions

    CN112655104A

  • Double-resin-system composite graphite for bipolar plate of fuel cell as well as preparation method and application of double-resin-system composite graphite

    CN114976096A

  • Graphite modified material, graphite-based negative electrode active material and preparation method and application thereof

    CN115172743A

  • Preparation method of graphite-carbon nanofiber foam bipolar plate and bipolar plate

    CN117747864A

  • Low-resistivity carbon paste through hole circuit board and preparation method thereof

    CN118714734A